2016
DOI: 10.5039/agraria.v11i2a5362
|View full text |Cite
|
Sign up to set email alerts
|

Selection of mycorrhizal fungi for the initial growth of Albizia polycephala

Abstract: The use of inoculant mycorrhizal fungi brings several benefits to plants and may contribute to the production of high-quality and low-cost forest seedlings. Thus, the aim of this study was to evaluate the contribution of different species of mycorrhizal fungi to the initial growth of seedlings of Albizia polycephala. The experiment was evaluated every two weeks for a total period of 135 days. A randomized block design was established with nine replications and six treatments where there was one control (absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
1
1
0
1
Order By: Relevance
“…This suggested that the same effect probably would happen in this experiment by extending the plant observation time and the differences would become significant. Besides the experiment of Oliveira et al (2009), similar results were verified by Dos Santos et al (2016), studying AMF effects on a leguminous species called Albizia polycephala, where they found that Acaulospora colombiana (AMF species) had increased positively and significantly the neck diameter, leaf size and dry matter. On the other hand, it hadn't increased significally the height at 135 days of experiment, although it had shown an increase in height of 20% more than non-inoculated plants.…”
Section: Resultssupporting
confidence: 67%
“…This suggested that the same effect probably would happen in this experiment by extending the plant observation time and the differences would become significant. Besides the experiment of Oliveira et al (2009), similar results were verified by Dos Santos et al (2016), studying AMF effects on a leguminous species called Albizia polycephala, where they found that Acaulospora colombiana (AMF species) had increased positively and significantly the neck diameter, leaf size and dry matter. On the other hand, it hadn't increased significally the height at 135 days of experiment, although it had shown an increase in height of 20% more than non-inoculated plants.…”
Section: Resultssupporting
confidence: 67%
“…In another study, Silva et al (2016) showed a decrease in mycorrhizal colonization in Cecropia pachystachya Trécul with increasing P levels in the soil, but without affecting the height, stem diameter, biomass, and phosphorus levels in the aboveground parts of the plants. On the contrary, the maintenance of a high root colonization rate at high P doses is indicative of high mycorrhizal dependence of the tree species (Santos et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Entre eles, pode-se observar resultados positivos, neutros e negativos da prática. Desse modo, ressalta-se que entre os fatores que podem determinar o efeito da associação planta x FMA destacam-se o teor de nutrientes no solo, em especial o P, assim como a espécie vegetal e o microrganismo envolvidos na associação (Santos et al, 2016). Soares et al (2017) encontraram resposta negativa da inoculação com Glomus clarum e Gigaspora margarita em mudas de Anadenanthera colubrina, observando redução no crescimento, produção de massa e qualidade das mudas produzidas em substrato inoculado.…”
Section: Fungos Micorrízicos Arbusculares (Fma) E Produção De Mudas D...unclassified